THE CONCEPT OF AKHLAQ ACCORDING TO SHEIKH MUHAMMAD AL-UTHAYMEEN: IMPLEMENTATION IN DA'WAH AND EDUCATION IN THE DISRUPTION ERA - Abdurrahman; Samsuddin; Agusman; Abdul Jabar Idharudin (International Journal of Multidisciplinary Reseach, 2025)
The era of disruption, marked by the rapid transformation of technology and social change, has significantly impacted the ethical values and spirituality of Muslims, particularly in the context of education and da’wah. In this situation, there emerges an urgent need to re-explore authentic and contextual concepts of Islamic morality (akhlak). This study aims to deeply analyze the thoughts of Shaykh Muhammad Al-Uthaymeen on Islamic ethics and evaluate their relevance in the practice of da’wah and Islamic education in the disruption era. Using a narrative review approach and conceptual paper strategy, this study processes secondary data sourced from Al-Uthaymeen’s works and related academic literature through content and thematic analysis techniques. The findings indicate that the concept of ethics according to Al-Uthaymeen is strongly rooted in tawhid (monotheism) and servitude to Allah, with an emphasis on character building through education and an ethical, communicative, and wise approach to da’wah. His thoughts are proven relevant in addressing challenges of digital ethics and moral degradation in contemporary society. This study contributes conceptually to the development of Islamic ethical studies and encourages the reorientation of education and da’wah strategies that are adaptive to the digital social context. The implications of this research highlight the need for integrating tawhidi-based moral values into educational curricula and the development of digital da’wah guidelines grounded in Islamic ethical principles.